Satire and Sarcasm on the “YouTube Got Talent" Video: A Case Study on Skinnyindonesian24 Channel - Kasno Atmo Sukarto; Fachrizah Fauziah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The specialty of the satire language style can be seen through the use of figurative words in it. The more a person is able to use words, it is able to create a special impression when telling someone who is the target of the satire. This study aims to describe the forms and functions of satire and sarcasm in the video content SkinnyIndonesian24 "YouTube's Got Talent". The method used is a qualitative descriptive research method. The data was obtained by using the free-of-conversation (SBLC) listening technique using Gorys Keraf's theory. The results obtained in this study are 29 satirical satire language styles that satirize YouTubers, Netizens, and the YouTube algorithm, and 7 sarcasm styles that satirize YouTubers, Netizens and the jury. The function of the satire language style is 9, and the sarcasm style is 4. Based on the data that the writer finds, the satirical style of satire seems to be more dominant than the sarcasm style. However, it has many of the same functions that are as opinion delivery.